সৌরভে গৌরবে ঢাকা বিশ্ববিদ্যালয় : অ্যালামনাই মহামিলন ২০০৯ - আহমেদ, রকীবউদ্দীন
Contributed articles by former students of the University of Dhaka, Bangladesh, about their university and the alumni; souvenir volume released during a conference held in the university in 2009, on the occasion of completion of sixty years of its Alumni Association; conference organized by the association.